(untitled) (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2025)
The article systematizes and comprehensively analyzes the phenomena of the phonetic level of the Internet vocabulary of the modern Kazakh language. Instagram, Facebook, social networks (Threads, Instagram, Facebook), and instant messengers (WhatsApp, Telegram), which have been actively used in recent years, were chosen as the object of the study. The research used methods of observation, generalization, comparative and descriptive analysis. As a result, it is revealed that new forms of linguistic usage are being formed in the Internet space, characterized by a mixture of elements of spoken and written speech. At the phonetic level, phenomena such as sound compression of words and, conversely, the repetition of graphemes to convey emotions in writing are widespread. The active use of Latin graphics and the development of foreign-language sounds indicate a new stage of phonetic adaptation in the Kazakh-speaking Internet space. The article provides specific examples of these phenomena, reveals their causes and impact on the modern linguistic norm and writing culture. According to the results of the study, it was found that the phonetic features of the Internet vocabulary reflect the natural development and adaptability of the Kazakh language.